Pengaruh ROA, ROE, EPS, dan PER Terhadap Harga Saham Perusahaan Pertambangan Sub Sektor Coal Mining di Bursa Efek Indonesia Tahun 2018-2022 - Kosasih; Isah Amini Yasmin (Masyarakat Ekonomi Syariah Bogor, 2024)
The mining sector, particularly coal mining, has experienced a decline in revenue and share prices over the period 2018-2022. This decline occurred concurrently with the global pandemic. Subsequent to the pandemic, there has been a notable rise in both revenue and share prices. This research aims to examine the connections between the ratios of ROA, ROE, EPS, and PER in relation to the variations in stock prices within the coal mining sub-sector on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. A quantitative method was selected as the research approach. The analysis was conducted using multiple regression with the SPSS 27 tool. Data collection involved a mix of documentation, literature study, and literature review methods. The sampling technique employed was purposive sampling. Partial results were obtained, ROA has a negative though insignificant impact on stock prices of the coal mining subsector during the period 2018-2022, Furthermore, ROE has a positive though insignificant impact on stock prices. Meanwhile, EPS and PER have a statistically significant yet positive impact on the stock prices of this sector during the same period. Also simultaneous analysis revealed that ROA, ROE, EPS, and PER are collectively associated with a statistically significant effect on stock prices.